2020
DOI: 10.3390/md18010058
|View full text |Cite
|
Sign up to set email alerts
|

Shellmycin A–D, Novel Bioactive Tetrahydroanthra-γ-Pyrone Antibiotics from Marine Streptomyces sp. Shell-016

Abstract: Four novel bioactive tetrahydroanthra-γ-pyrone compounds, shellmycin A–D (1–4), were isolated from the marine Streptomyces sp. shell-016 derived from a shell sediment sample collected from Binzhou Shell Dike Island and Wetland National Nature Reserve, China. The structures of these four compounds were established by interpretation of 1D and 2D NMR and HR-MS data, in which the absolute configuration of 1 was confirmed by single crystal X-ray diffraction, and compound 3 and 4 are a pair of stereoisomers. Compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Four compounds, shellmicin A-D isolated from the Streptomyces sp. shell-016 were described as cytotoxic agents against five human tumor cell lines: non-small cell lung cancer (H1299, ATCC CRL-5803), malignant melanoma (A375, ATCC CRL- 1619), hepatocellular carcinoma (HepG2, ATCC HB-8065), colorectal adenocarcinoma (HT29 ATCC HTB-38), and breast cancer (HCC1937, ATCC CRL-2336) [ 55 ]. Moreover, the compounds Shellmicin A, B, and D showed greater cytotoxicity (IC 50 ranging from 0.69 μM to 3.11 μM at 72 h) than Shellmicin C. Interestingly, shellmicin C and D are a pair of stereoisomers, and their biological activity differ considerably.…”
Section: Resultsmentioning
confidence: 99%
“…Four compounds, shellmicin A-D isolated from the Streptomyces sp. shell-016 were described as cytotoxic agents against five human tumor cell lines: non-small cell lung cancer (H1299, ATCC CRL-5803), malignant melanoma (A375, ATCC CRL- 1619), hepatocellular carcinoma (HepG2, ATCC HB-8065), colorectal adenocarcinoma (HT29 ATCC HTB-38), and breast cancer (HCC1937, ATCC CRL-2336) [ 55 ]. Moreover, the compounds Shellmicin A, B, and D showed greater cytotoxicity (IC 50 ranging from 0.69 μM to 3.11 μM at 72 h) than Shellmicin C. Interestingly, shellmicin C and D are a pair of stereoisomers, and their biological activity differ considerably.…”
Section: Resultsmentioning
confidence: 99%
“…Four compounds called shellmicin A-D isolated from the Streptomyces sp. shell-016 were described by (Yong Han et al 2020) and studied concerning cytotoxicity against five human tumor cells lines: non-small cell lung cancer (H1299, ATCC CRL-5803), malignant melanoma (A375, ATCC CRL-1619), hepatocellular carcinoma (HepG2, ATCC HB-8065), colorectal adenocarcinoma (HT29 ATCC HTB-38) and breast cancer (HCC1937, ATCC CRL-2336). The study indicated that the compounds Shellmicin A, B and D showed greater cytotoxicity than Shellmicin C compound, with an IC 50 ranging from 0.69 µM to 3.11 µM at 72 h. An interesting fact was that shellmicin C and D are a pair of stereoisomers and their biological activity was significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…Another example is tetrahydroanthra-γ-pyrone from marine Streptomyces sp. (isolated from Binzhou shell island), which presented activity against Bacillus subtilis, Staphylococcus aureus and Enterococcus faecalis with a minimum inhibitory concentration (MIC) from 3 to 46 μg/mL [26].…”
Section: Antibioticsmentioning
confidence: 99%